Combining flagellin and human β-defensin-3 to combat bacterial infections - Sabag, Ofra; Lorberboum-Galski, Haya (Frontiers in Microbiology, 2014)
The discovery and therapeutic use of antibiotics made a major contribution to the reduction of human morbidity and mortality. However, the growing resistance to antibiotics has become a matter of huge concern. In this study we aimed to develop an innovative approach to treat bacterial infections utilizing two components: the human antibacterial peptide β-defensin-3 (BD3) and the bacterial protein flagellin (F). This combination was designed to provide an efficient weapon against bacterial infections with the peptide killing the bacteria directly, while the flagellin protein triggers the immune system and acts against bacteria escaping from the peptide’s action. We designed, expressed and purified the fusion protein FBD3 and its two components, the F protein and the native BD3 peptide. FBD3 fusion protein and native BD3 peptide had antibacterial activity in vitro against various bacterial strains. FBD3 and F proteins could also recognize their receptor expressed on target cells and stimulated secretion of IL-8. In addition, F and FBD3 proteins had a partial protective effect in mice infected by pathogenic E. coli bacteria that cause a lethal disease. Moreover, we were able to show partial protection of mice infected with E. coli using a flagellin sequence from Salmonella. We also explored flagellin’s basic mechanisms of action, focusing on its effects on CD4+ T cells from healthy donors. We found that F stimulation caused an increase in the mRNA levels of the Th1 response cytokines IL12A and IFNγ. In addition, F stimulation affected its own receptor.